2010
DOI: 10.1243/09544100jaero655
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and experimental research of stall inception on subsonic axial-flow compressor rotor

Abstract: Three-dimensional flow simulation and blade tip high-response static pressure measurements were performed on an isolated subsonic compressor rotor to gain more insight into the stall inception mechanism of the compressors. The Navier—Stokes solver, EURANUS, was used for computation. The steady-state flow solution was achieved at the convergence of a four-stage explicit Runge—Kutta integration scheme. The time-dependent calculation was implemented in the implicit dual time stepping scheme, which allowed for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…1) Lu, et al [3] and Okada et al [4] presented a draft on "Stall Inception in Axial Flow Compressor". A comprehensive measurement and theoretical analyses was used to determine which of the two types of instabilities (rotating stall or surge) would occur in a particular situation.…”
Section: Other Approaches/techniquesmentioning
confidence: 99%
“…1) Lu, et al [3] and Okada et al [4] presented a draft on "Stall Inception in Axial Flow Compressor". A comprehensive measurement and theoretical analyses was used to determine which of the two types of instabilities (rotating stall or surge) would occur in a particular situation.…”
Section: Other Approaches/techniquesmentioning
confidence: 99%
“…3D unsteady Reynolds-averaged Navier-Stokes (URANS) methods have been successfully applied to simulation of rotating stall phenomenon in compressors [3]~ [12], and most of the studies concentrated on rotors or single-stage compressors. It is pointed by Wu [12] that, flow characteristics of rotating stall in single-row environment are different from that in multi-row environment.…”
Section: Introductionmentioning
confidence: 99%
“…It had been found that if the rotor tip clearance is small stall inception occurs at the hub, but at clearances typical for a multistage compressor the inception is at the tip. 9 The tip leakage vortex breakdown and shedding became violent, 10 which was the major characteristic in the compressor flow-field, 11–13 and it was the principal factor of flow instability. 14,15 The main reasons for compressor stall are the flow separation and the large range of the low-energy flow that occur at the tip of the rotor blade near the stall point.…”
Section: Introductionmentioning
confidence: 99%